Surface-enhanced Raman scattering (SERS) of Methyl Orange on Ag-DLC nanoparticles - Zarei, Arezou; Shafiekhani, Azizollah (Materials chemistry and physics, 2020)
In the present study, Ag nanoparticles were synthesized in amorphous hydrogenated carbon films on glass substrates by RF-PECVD and RF-sputtering co-deposition method at the room temperature. Methyl orange was utilized as an analyte with different concentrations on Ag nanoparticles that were embedded in diamond-like carbon (DLC). Ultraviolet–visible (Uv–vis) spectroscopy, XRD analysis, Raman spectroscopy, Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscopy (FESEM) were performed to characterize films. Ag-DLC with an average size of less than 14 nm was the active site for surface-enhanced Raman scattering (SERS). Sensitivity of measurements in SERS spectra was increased by these types of thin films. This method of nano-particle synthesis is cost-effective and just requires a one-step synthesis. Such substrates can be used for several times. Moreover, they are useful for biosensors because of their hardness and other properties that may be subsequently referred. •Ag nanoparticles were synthesized in DLC on glass substrates.•Sensitivity of SERS increased by Ag-DLC.•Such substrates can be used for several times.•This type of Ag-DLC could be used as biosensor.